2013
DOI: 10.1186/1747-597x-8-33
|View full text |Cite
|
Sign up to set email alerts
|

Development of an integrative cessation program for co-smokers of cigarettes and cannabis: demand analysis, program description, and acceptability

Abstract: BackgroundTobacco and cannabis use are strongly interrelated, but current national and international cessation programs typically focus on one substance, and address the other substance either only marginally or not at all. This study aimed to identify the demand for, and describe the development and content of, the first integrative group cessation program for co-smokers of cigarettes and cannabis.MethodsFirst, a preliminary study using expert interviews, user focus groups with (ex-)smokers, and an online sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 39 publications
0
29
0
1
Order By: Relevance
“…However, cessation programs that exclusively address tobacco consumption appear to be less effective for individuals who also consume cannabis . In fact, evidence is accumulating that suggests that simultaneous tobacco and cannabis abstinence predicts better treatment outcomes …”
Section: Conclusion Recommendations and Future Directionsmentioning
confidence: 99%
“…However, cessation programs that exclusively address tobacco consumption appear to be less effective for individuals who also consume cannabis . In fact, evidence is accumulating that suggests that simultaneous tobacco and cannabis abstinence predicts better treatment outcomes …”
Section: Conclusion Recommendations and Future Directionsmentioning
confidence: 99%
“…In addition, participants' high levels of satisfaction (based on their recommendation levels) illustrated acceptability. A more detailed evaluation of intervention acceptability is presented in an earlier publication [22]. We did not find evidence of hospitalisation due to course participation and only three participants indicated that severe problems due to their simultaneous cessation (attempts) were among their reasons for discontinuing the intervention.…”
Section: Discussionmentioning
confidence: 93%
“…Finally, an information evening was offered. The publication regarding the development of the intervention provides a detailed description of the recruitment process [22].…”
Section: Study Design and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, concurrent cannabis and tobacco use is associated with poor treatment outcomes during both cannabis (Haney et al, 2013; Moore and Budney, 2001) and tobacco interventions (Patton et al, 2005; Stapleton et al, 2009), with some evidence suggesting that individuals may compensate for abstinence from one substance by increasing their use of the other (Allsop et al, 2012). Although interventions adapted to address concurrent cannabis and tobacco use have shown initial efficacy (Becker et al, 2014; Becker et al, 2013; Gulliver et al, 2015), there is a need for more effective treatment approaches. The current data suggest that a focus on other psychosocial and psychiatric issues may further improve interventions targeted at reducing comorbid tobacco and cannabis use, particularly among women who quit smoking tobacco during pregnancy.…”
Section: Discussionmentioning
confidence: 99%